CRENÇAS E ATITUDES LINGUÍSTICAS DE DESCENDENTES DE IMIGRANTES ITALIANOS DE PINHO DE BAIXO, IRATI, PARANÁ - ROSSA, ROSANA TAÍS (2017)
This work, based on the assumptions of the Variacionist Sociolinguistics and the studies about beliefs and linguistic Attitudes, has as its main objective to present and analyze positive and negative linguistic beliefs and attitudes of descendants of Italian immigrants from the community of Pinho de Baixo, located in the countryside of Irati / PR. Considering that this locality is formed mainly by descendants of immigrants and due to the fact that the influences of the city are increasingly entering the countryside, we seek to understand how the population perceives the Portuguese language with the italian accent and expressions in the Italian language spoken by the members of the community, as well as to understand the way it reacts to this language. The text is divided into five chapters: the first chapter discusses the role of language in society, the first linguistic studies, how Sociolinguistics arose and how it branched out; the second chapter discusses the types of linguistic variation and the metalanguage used to refer to them, and also exposes the concept, process and consequences of linguistic change and discusses linguistic prejudice; in the third chapter of the work we explore linguistic beliefs and attitudes, studying them individually, according to the conception that belief consists of thought and attitude is manifested by action. Still in this chapter, we lead some reflections about identity, culture and representation; in the fourth chapter we present the context of Italian immigration in Brazil, the investigated community and our informants. We explain the methods we used to conduct the research and list the questions we applied in interviews. Finally, in the last chapter, we show the analysis of the data, intercalating quantitative data and interviews excerpts. Among the results obtained during the investigation, we can highlight that the Italian language formerly spoken by the residents is ending, whereas today only a small part of the community still has daily practices that involve this language. The folk group formed by the residents of Pinho de Baixo seeks to rescue Italian culture, but the strong interference of urbanization has turned it into a difficult task.